EFFECT OF Archidendron pauciflorum IN DIET ON HEMATOLOGY, GLUCOSE, LIVER FUNCTION, AND WEIGHT INDUCED-RATS WITH HIGH-FAT DIET - Hilmi Al Wahid; Aziiz Mardanarian Rosdianto; Ronny Lesmana (JURNAL ILMU FAAL OLAHRAGA INDONESIA, 2021)
A. pauciflorum is known to have various pharmacological activities, including antimicrobial, antioxidant, antidiabetic, antidiarrheal, anticancer, and anti-gastric activity. In-vivo studies were conducted to determine the therapeutic and metabolic effects of A. pauciflorum. This research aimed to study the Effect of A. pauciflorum added to the diet in rats. The treatment group was divided into 4 to six mice each. The treatment group consisted of normal control, a negative control, and two test groups. The normal control group was given a normal diet (NCD), and the negative control group was given a high-fat diet (HFD) diet containing palmitic fatty acid to be overweight. Both test groups were given a normal diet and preparations containing A. pauciflorum (NCD-JK), and high-fat diets were fed with A. pauciflorum (HFD-JK). The treatment was carried out for nine weeks. Adding A. pauciflorum to feed can increase hemoglobin, RBC, WBC, glucose, and body weight caused by the content of Se in A. pauciflorum, which can protect cells from free radicals and affect the composition of gut microbiota. However, the administration of A. pauciflorum did not affect the platelets, ALT, and AST levels, which might be due to the lack of Se content in A. pauciflorum.